Layered Na2RuO3 as a cathode material for Na-ion batteries - Tamaru, Mao; Wang, Xianfen; Okubo, Masashi; Yamada, Atsuo (Electrochemistry communications, 2013)
Na-ion batteries have attracted much interest recently due to strong industrial demands for inexpensive and efficient energy storage. Although layered NaxMO2 (0<x<1, M: transition metal) is the subject of intense studies as cathode materials for the Na-ion batteries, the electrochemical properties of layered Na2MO3 have not been clarified to date. The present work demonstrates that Na2RuO3 can show reversible Na-ion insertion/extraction leading to the specific capacity of 140mAhg−1 at the average potential of 2.8V vs. Na/Na+. Both the capacity retention and Coulombic efficiency are kept at almost 100% during 20cycles, which suggests high reversibility of the electrochemical reaction. Due to the fast Na-ion diffusion and metallic conduction, Na2RuO3 can show the excellent rate capability, where 53% of the maximum discharge capacity is retained even at a high discharge rate of 5C. [Display omitted] •We report Na2RuO3 as a cathode material for Na-ion batteries.•Na2RuO3 delivers 140mAhg−1 at the average potential of 2.8V vs. Na/Na+.•Na2RuO3 shows excellent rate capability leading to 53% capacity retention at 5C.